'This sperm hits the bullseye': Bollywood, youth and male (im)potency as a neoliberal game. Issue 1 (1st November 2020) - Chakrabarti, Baidurya
This article, by closely examining the trajectory of the upcoming Bollywood star Ayushmann Khurrana, tries to unravel the constitutive fantasies that provide a significant degree of coherence to his star-image. Through a close textual reading, the article aligns these fantasies with the diurnal realities of neoliberal India. In these fantasies, the male protagonist is found to be (a) the privileged embodiment of a surplus/lack that comes to signify the 'thing' called the modern, but (b) the man and his sociality is not prepared yet to accept this 'thing', thus triggering comedy; it is only in romantic conjugation with (c) a working woman can this excess charge of the modern be resolved within the narratives. Using psychoanalytic insights, the article unpacks these fantasies as ones involving both a crisis and an ultimately infantile reaction to it.